Критерій енергетичної еквівалентності для оцінки ЕМС при рефармінгу радіочастотного спектру - Чурсанов, М. О. (ХНУРЕ, 2022)
The criterion of energy equivalence for estimation of EMC at reforming of a radio frequency spectrum is offered. The essence of reforming is the possibility of additional use of previously allocated radio frequency bands by newer cellular technology. As a result of such a procedure, several technologies can be combined in one frequency range.